2000
DOI: 10.1677/joe.0.1650399
|View full text |Cite
|
Sign up to set email alerts
|

Localisation and temporal changes in prostaglandin G/H synthase-1 and -2 content in ovine intrauterine tissues in relation to glucocorticoid-induced and spontaneous labour

Abstract: Parturition in the ewe is preceded by an increase in the synthesis of prostaglandins (PGs) by gestational tissues. To establish the uterine source of these PGs, placental cotyledons, fetal membranes and maternal uterine tissues were collected from ewes (n=6) at spontaneous parturition. Solubilised tissue extracts were prepared and analysed by Western blots using polyclonal antibodies to PG G/H synthase-1 and -2 (PGHS-1 and PGHS-2). PGHS-1 was expressed by all intrauterine tissues at term labour. Densitometric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…In ovine foetal membranes, levels of PTGS1 were highest within the amnion (e.g. w25-fold higher than in the chorion) (McLaren et al 2000). PTGS1 was also found to be highly expressed within the guinea pig amnion, and its preferential inhibition was associated with prolonged gestation (Welsh et al 2005).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…In ovine foetal membranes, levels of PTGS1 were highest within the amnion (e.g. w25-fold higher than in the chorion) (McLaren et al 2000). PTGS1 was also found to be highly expressed within the guinea pig amnion, and its preferential inhibition was associated with prolonged gestation (Welsh et al 2005).…”
Section: Introductionmentioning
confidence: 95%
“…The increasing production of PGs by the feto-placental tissues during the 15-20 days prior to parturition is key to the successful initiation and progression of labour in the ewe (Olson et al 1985, Thorburn 1991, Gyomorey et al 2000. The increased production of PGs in intrauterine tissues towards the end of gestation could (at least in part) be due to increased expression/activity of PTGS1 and PTGS2 (McLaren et al 2000, Whittle et al 2000.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in fetal cortisol production is a key element in the signalling pathway which leads to parturition in sheep via induction of placental enzymes that redirect steroidogenic pathways to favour the production of oestrogen at the expense of progesterone (Anderson et al 1975, Steele et al 1976). This change in progesterone/oestrogen ratio activates COX-2, ultimately leading to an increase in PG production (McClaren et al 1996(McClaren et al , 2000. However, Whittle et al (2000) showed that infusion of cortisol into the fetus beginning on day 125 of pregnancy increased both expression of COX-2 mRNA in placental trophoblast tissue and levels of fetal plasma PGE 2 , even in the prescence of the aromatase inhibitor 4-OHA.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments using both gene-deletion and pharmacological treatments with specific COX-1 and COX-2 inhibitors have shown that parturition in mice is normally dependent on upregulation of COX-1 in the endometrium (Gross et al 1998, Reese et al 2000, Loftin et al 2002. In the ewe, however, COX-2 expression in the endometrium is increased during both spontaneous and dexamethasone (DEX)-induced labour, whereas there is no change in COX-1 expression at this time (Zhang et al 1996, Gibb et al 2000, McClaren et al 2000. In the uterus and placenta PG production and release can be modulated by a variety of physiological and pharmacological stimuli, for example oxytocin (OT; Lee and Silvia 1994), lipopolysaccharide (LPS;Flynn & Hoff 1995), calcium ionophore (CaI; Poyser 1987) and glucocorticoids (Whittle et al 2001).…”
Section: Introductionmentioning
confidence: 99%